The Effect of Health Education on Dietary Knowledge and Practices of Pregnant Women in Jordan: A Quasi-Experimental Study - Abu-Baker NN; Abusbaitan HA; Al-Ashram SA; Alshraifeen A (Dove Medical Press, 2021)
Nesrin N Abu-Baker,1 Hanan A Abusbaitan,1 Safa A Al-Ashram,2 Ali Alshraifeen3 1Faculty of Nursing, Community and Mental Health Nursing Department, Jordan University of Science & Technology, Irbid, Jordan; 2Consultantation, Secretary General-Civil Service Bureau, Amman, Jordan; 3Faculty of Nursing, Department of Adult Health Nursing, The Hashemite University, Zarqa, JordanCorrespondence: Nesrin N Abu-BakerFaculty of Nursing, Community and Mental Health Nursing Department, Jordan University of Science & Technology, P.O Box 3030, Irbid, 22110, JordanTel +962 2 7201000 Ext. 23620Fax +962 2 7201065Email nesrin@just.edu.joBackground: Evidence reported inadequate dietary practices among pregnant women and recommended educating pregnant women about their diet to improve pregnancy outcomes. However, studies examining the effect of health education about dietary practices during pregnancy are lacking in Jordan.Objective: To examine the effect of health education on the levels of dietary knowledge and practices among pregnant women in Jordan.Methods: A quasi-experimental design (pretest-posttest control group) was used. A consecutive sample of 195 pregnant women was recruited from four public health centers in Jordan; two health centers formed the intervention group (n=95) and two formed the control group (n=100). A structured questionnaire was used to assess dietary knowledge and practices before and after the intervention. The intervention group received health education for one month, while the control group received routine antenatal care. Data were collected from September to November 2019.Results: After health education, the intervention group recorded significantly higher dietary knowledge score (mean= 19.30, SD= 0.88) compared to the control group score (mean= 14.36, SD= 2.11), p < 0.001. In addition, the intervention group reported significantly higher dietary practices score (mean= 8.70, SD= 1.16) compared to the control group score (mean= 7.02, SD= 1.66), p < 0.001. In particular, the intervention group recorded a significant increase in dietary knowledge score from the pretest (mean= 14.60, SD= 2.53) to posttest (mean= 19.30, SD= 0.88), as well as practices score from the pretest (mean= 6.69, SD= 1.97) to posttest (mean= 8.70, SD= 1.16), p < 0.001.Conclusion: Providing health education concerning dietary knowledge and practices in the care of pregnant women may improve their knowledge and practices. Nurses and midwives in primary care centers have an essential role in assessing this knowledge and providing health education for pregnant women.Keywords: dietary knowledge, dietary practices, health education, pregnant women, Jordan